Analisis HBU dan Peluang Kejenuhan Lalu Lintas pada Pengembangan Plasa Simpang Lima Semarang - Alberta Kristi Purwandari; Agung Sugiarto; Lintang Jata Angghita (Soegijapranata Catholic University, 2023)
Simpang Lima Plaza is a Semarang City Government asset which is located in the city center, precisely on Jalan Ahmad Yani, Semarang City. The Plaza Simpang Lima building was built in 1990 with a building area of 38,935 m2. Plaza Simpang Lima is managed by PT Argamukti with a 30 year contract system which will end in 2024. When the contract ends, the age of the Plaza Simpang Lima building will be 30 years, so the use of the Plaza Simpang Lima building needs to be reviewed in relation to its potential utilization. Previous research discussed asset optimization but ignored the impact on traffic potential of selected land uses. This research was conducted to find out the most effective land optimization and the resulting traffic impacts. In this research the analysis was carried out using the Highest and Best Use method to determine alternative uses that are appropriate and technically and financially possible to determine the optimum value and the trip generation method to determine the potential traffic impacts that occur from the selected land use. The results of this research were obtained that the alternative effective use of land is a mall which will result in an increase in land value in the 7 year projection period of IDR 379,259,450,817 with an increase in roundabout delays of 35.23% and the chance of this condition occurring is 36.2%.